Application of the Bale Meten Architectural Concept on the Spatial Order Jeroan of Pura Mertasari Denpasar - Mahaputra, Bayu; Mariada Rijasa, Made; WItarka Yudiata, Ketut (Universitas Ibn Khaldun Bogor, 2023)
Pura Mertasari is a temple located on Jalan Kepundung, Denpasar-Bali. The spatial concept of this temple is tri mandala, with the main zone functioning as the offal, the middle zone functioning as the middle jaba and the nista zone functioning as the jaba sisi. However, in addition to the macro spatial division, the uniqueness of the micro spatial division of the jeroan pura was found. The spatial division in the jeroan of this temple is called the architectural concept of bale meten. The bale meten architectural concept is a unique concept. However, a problem was found, namely there has been no similar research that examines this concept. Thus, departing from the aim of enriching scientific studies of Balinese architecture which is applied to the spatial of temples and the desire to study the architectural concept of bale meten on the spatial of temple innards scientifically, this research needs to be carried out. So that in the future this research can be used as reading material and knowledge about the application of the architectural concept of bale meten in the spatial of temple innards. This research method is descriptive qualitative with a case study approach. The result of the research is that the innards of the temple are manifested like the concept of the bale meten space. This finding is confirmed by the division of three elements of the spatial hierarchy, namely the main function as gedong in the bale meten and as a spatial pelinggih on the innards of the temple, madya as the terrace of the owner of the house in the bale meten and as the canopy of pelinggih / place to put ceremonial facilities on the innards of the temple, and nista as the visitor's terrace in the bale meten and as a place for pengempon in the jeroan of pura.